Make experience by the teacher of the early grades of Elementary School in the context of the current educational policies (Práxis Educativa, 2020)
In this article, a discussion about the conditions that teachers of the early grades of Elementary School have to make experience in the school space, weakened by conservative policies, and about professional development through this experience is presented. John Dewey and Jorge Larrosa’s assumptions provide support for the comprehensive perspective that identifies teacher training as a successive process of making experience. The procedures for data collection, analysis and interpretation are close to the principles of the comprehensive interview, proposed by Kaufmann. Thirteen interviews were conducted with public school teachers. The results point to the teaching scenario of these teachers marked by the feeling of struggle for the dignity of their work: while the characteristic pressures and restrictions of the school space in which they operate disturb them, they also reveal opportunities for them to affirm themselves professionally.Keywords: Conservative policies. Experience. Early grades of Elementary School.